2020
DOI: 10.1292/jvms.19-0078
|View full text |Cite
|
Sign up to set email alerts
|

Effects of clamping umbilical cord on the neonatal viability of puppies delivered by cesarean section

Abstract: In human neonates, when the umbilical cord is kept intact postpartum, blood continues to flow to the neonate, but this procedure might be difficult in dogs owing to a shorter umbilical cord and several neonates in a litter. However, it might be possible to detach the placenta and keep the umbilical cord intact, allowing residual blood to flow to the puppies. This study compared the effects of clamping versus no clamping of the umbilical cord in dogs born by cesarean section on neonatal vitality. The puppies we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…Our Apgar score results at 0 min were much lower than those reported by Vilar et al [ 22 ], however, it might be due to the different surgical and anesthetic protocols used or the exact time of the initial Apgar assessment, which in our study was performed prior to any medical attention provided for a newborn. The exact time of cord clamping could also influence the neonatal state as reported by Pereira et al who described a higher vitality in puppies in which the umbilical cord was preserved intact for a least 3 min after birth to allow the residual blood to flow to the puppies [ 23 ]. On the other hand, Davidson [ 1 ] suggested that neonates delivered via Cesarean section tend not to initiate respiration spontaneously, which may affect their initial Apgar score records.…”
Section: Discussionmentioning
confidence: 99%
“…Our Apgar score results at 0 min were much lower than those reported by Vilar et al [ 22 ], however, it might be due to the different surgical and anesthetic protocols used or the exact time of the initial Apgar assessment, which in our study was performed prior to any medical attention provided for a newborn. The exact time of cord clamping could also influence the neonatal state as reported by Pereira et al who described a higher vitality in puppies in which the umbilical cord was preserved intact for a least 3 min after birth to allow the residual blood to flow to the puppies [ 23 ]. On the other hand, Davidson [ 1 ] suggested that neonates delivered via Cesarean section tend not to initiate respiration spontaneously, which may affect their initial Apgar score records.…”
Section: Discussionmentioning
confidence: 99%
“…All the EMCSs were performed at dystocia occurrence. Dystocia was diagnosed in the following conditions: green or black vaginal discharge, unsuccessfully strains for more than 30 min, interval of maximum 3 h between puppies’ expulsion, presence of fetal distress (heart rate < 180 bpm), narrow birth canal, fetal obstruction, uterine inertia [ 6 , 20 , 21 , 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…Although puppies and kittens can present physiological hypoxia, demonstrating hypercapnia and mixed acidosis during parturition and immediately after birth, this is transient [ 46 , 47 , 48 , 49 , 50 ]. This occurs because the fetus undergoes a short period of asphyxia simultaneous with uterine contractions, which culminates in a decrease in uterine blood flow, placental perfusion, and gas exchange [ 20 , 48 ].…”
Section: Fetal-neonatal Transitionmentioning
confidence: 99%
“…This occurs because the fetus undergoes a short period of asphyxia simultaneous with uterine contractions, which culminates in a decrease in uterine blood flow, placental perfusion, and gas exchange [ 20 , 48 ]. Adaptation to pulmonary breathing after birth is essential for CO 2 elimination and acid–base balance recovery [ 46 , 47 , 48 , 49 , 50 ]. However, any form of dystocia can worsen asphyxia, resulting in excessive hypoxia and leading to high mortality rates in the first few days after birth [ 10 , 20 ].…”
Section: Fetal-neonatal Transitionmentioning
confidence: 99%
See 1 more Smart Citation